Maharah Kalam And It's Problem - Sa'diyah, Khalimatus; Ahsan, Mariana Rizqi; Ulinnuha, Muhammad Afthon ((الطموحات ) EL-THUMUHAT, 2024)
Maharah kalamis the ability to express ideas or ideas through articulate sounds that aim to provide understanding through two-way communication using language as the medium. In the context of learning Arabic, maharah kalam is one of the basic skills that students must master. But unfortunately, most students experience difficulties in speaking Arabic, this is caused by various factors such as nervousness in speaking, lack of mastery of mufrodat, the lingering accent of the local language, and learning methods that are too monotonous. The solutions to these problems are divided into two parts, namely from the teacher and students, while the solution made by the teacher is to improve the quality of learning. A teacher must always motivate his students the importance of mastering maharah al-kalam, to create a pleasant atmosphere a teacher is required to master four competencies, the teacher should use a variety of methods, the teacher himself should have the initiative to create a language environment, especially Arabic. While the solution from the students is that students are more active in learning maharah al-kalam by frequently practicing reciting the hijaiyyah letters from makhroj according to the correct instructions, and learning Arabic vocabulary little by little. Keywords: maharah kalam, probematics